Multi-sensory ethnography and vertical urban transformation: ascending the Peckham Skyline. (4th May 2021) - Jackson, Emma; Benson, Michaela; Calafate-Faria, Francisco
ABSTRACT: In this paper, we offer a conceptual and methodological intervention that demonstrates how multi-sensory ethnography might enrich critical analysis of vertical urban transformation. Through the lens of two sites in Peckham, southeast London – a multi-storey car park and an ex-industrial warehouse complex – recently remade as leisure and retail spaces, we examine how processes and practices by which these spaces at height are designed and curated reproduce social and spatial inequalities. As we argue, in retraining the vantage point of research on verticality through attention to other senses – which we label here as non-ocular vistas – new perspectives and texture are brought to understandings of place-making, that address how power functions through the erection of physical, symbolic and sensory exclusions, and how sensorial clashes makes visible contestations over space in a changing urban environment. In this way, our contribution: (1) privileges a multi-sensory perspective in understanding how power is reproduced in and through the vertical transformation of the city; (2) intervenes in research on verticality to centre the concept of non-ocular vistas; and (3) offers a methodological innovation that make visible the subtle affects that manifest the politics of exclusion within spaces at height.